Relationship Between Knowledge Level and Social Media Influence Toward Consumption Behavior of Foods with Diabetes Mellitus Risk Among Pharmacy Students of Politeknik Harapan Bersama Tegal Class of 2021 - Ayu Lestari, Elita Diyani; Barlian, A. Aniq; Santoso, Joko (Universitas Ibn Khaldun Bogor, 2024)
Diabetes Mellitus or DM is a condition characterized by high levels of glucose in the blood and shows an increasing number of sufferers worldwide. The purpose of this study was to determine the relationship between the level of knowledge and the influence of social media towards the consumption behavior of foods with diabetes mellitus risk among pharmacy students of Politeknik Harapan Bersama Tegal class of 2021. This study took 103 students as sample. This research was conducted using quantitative correlation method. Data were analyzed using univariate analysis and multiple linear regression, as well as hypothesis testing using T-test, F-test, and coefficient of determination test. The results showed the level of knowledge and the influence of social media correlated the consumption behavior of foods with diabetes mellitus risk in Harapan Bersama Tegal Polytechnic Pharmacy students class of 2021.